Fatigue strength evaluation of a 13%Cr supermartensitic stainless steel by the thermographic method - Tavares Sérgio S.M. (EDP Sciences, 2021)
The fatigue limits of a 13Cr super-martensitic stainless steel from a hot rolled seamless tube were determined for three heat treatment conditions, including the as received quenched and tempered (QT) condition, quenched (Q), and quenched and double tempered (Q-DT). These heat treatments were applied to produce different microstructures and different tensile mechanical properties. The microstructures were characterized by microscopy and magnetic methods. The fatigue strength was accessed through the utilization of the thermographic technique. The results show that fatigue limits measured were between 38% and 44% of the ultimate strength. The as quenched condition gave the higher fatigue limit (444 MPa). However, the material has the lower dutility at this condition. The results aid to decide the best heat treatment condition and give support to design in applications where dynamic loadings are expected